(untitled) (Altre Modernità, 2018)
1950 was a pivotal year in the production and release of British London-set films. Ealing studios released The Blue Lamp (Basil Dearden, 1950) in January 1950, while Ealing’s The Lavender Hill Mob (Charles Crichton, 1951) and Pool of London (Basil Dearden, 1951) went into production in the same year. Then, in June 1950, Twentieth-Century Fox released Anglo-American production Night and the City (Jules Dassin, 1950). For critics, The Blue Lamp sealed Ealing’s reputation to capture a recognisable London, rooted in specific districts with ‘ordinary’ inhabitants with a community ethos. The Blue Lamp set the barometer for London-set films to follow. Indeed, British critics derided Night and the City as an inauthentic depiction of London, one created by ‘outsider’ Jules Dassin, in comparison to Ealing’s ‘familiar’ London. This paper firstly examines of archival documents of the production of location shooting in The Blue Lamp, to demonstrate how the film sealed Ealing’s reputation to capture a recognisable London, rooted in specific districts with ‘ordinary’ inhabitants with a community ethos. It then examines and compares the critical reception of The Blue Lamp and Night and the City, to explore discourses around ‘home-grown’ versus ‘outsider’ perceptions of London in the immediate postwar period.